Adsorptive removal of dimethyl disulfide from methyl tert-butyl ether using an Ag-exchanged ZSM-5 zeolite. Issue 95 (28th September 2016) - Zhao, Ya-wei; Shen, Ben-xian; Sun, Hui
Abstract : Ag + -exchange improves the DMDS adsorption amount by 7.7 times compared to parent HZSM-5. Abstract : Ion-exchange modification can largely change the adsorption ability of various adsorbents of zeolite. A series of Ag-exchanged ZSM-5 zeolites were prepared using an ion-exchange method and used to remove dimethyl disulfide (DMDS) from methyl tert -butyl ether (MTBE). The structural properties and acidity of the modified zeolite were examined using X-ray diffraction, N2 adsorption, NH3 -TPD and Py-IR. The effects of the ion-exchange level on DMDS adsorption were investigated. In addition, the adsorption isotherms and adsorption kinetic data were measured and interpreted. Introduction of Ag + into ZSM-5 contributes to the adsorption ability and increases the adsorption capacity by 7.7 times through enhancing the interactions between DMDS and zeolite. Strong acidity and Lewis acid sites are considered favorable for DMDS adsorption. The adsorption isotherms and kinetics results reveal that DMDS adsorption onto AgZSM-5 was endothermic chemisorption having an activation energy of 7.4 kJ mol −1 . The adsorbents can be regenerated at 300 °C in an air atmosphere.